Meningkatkan Hasil Belajar IPA melalui Model Inquiry pada Materi Perubahan Benda di SD An Nuriyah - Rosfiani, Okta; Sapitri, Intan; Rahman, Putri Aulia; Daulay, Raju Gusti; Fauzan, Ahmad; Habib, Izzul (TSAQOFAH, 2025)
The low learning outcomes of 6th grade students of SD Islam An-Nuriyah Jagakarsa on the material of changes in science subjects is the main problem of this study. In addition, traditional learning is less able to encourage critical thinking, critical thinking skills and problem-solving skills. The purpose of this study was to improve the learning outcomes of 6th grade students of SD Islam An-Nuriyah Jagakarsa on the material of changes in science subjects. To improve critical thinking, analytical skills, and problem-solving skills, science learning is very important. The inquiry-based learning model is used because it has the ability to encourage students to participate in the active learning process and explore the material independently. This study was designed as a classroom action research (CAR), with two cycles that include planning, implementation, observation, and reflection. The research instruments included observation sheets, learning outcome tests, and documentation. The results showed that student learning outcomes increased significantly. Although the average score of students was still below standard during the first cycle, they increased significantly during the second cycle. In addition, in activities such as asking questions, discussing, and experimenting, students showed an increase in desire and encouragement to participate. In conclusion, the inquiry-based learning model improves students' academic achievement in addition to improving their scientific process skills. There is evidence that implementing this model can significantly improve the quality of science learning in elementary schools.